Challenges in effective implementation of the surgical safety checklist and providing administrative solutions: A systematic qualitative review - Zahra Seyedghale; Marzieh Pazokian (Tehran University of Medical Sciences, 2019)
Background & Aim: The success of the surgical safety checklist in reducing surgical mortality and morbidity largely depends on the degree of compliance with the checklist and correct implementation of its components by the staff. The aim of this review is to determine the challenges of effective implementation of the surgical safety checklist and to provide solutions for its more effective implementation. Methods & Materials: In the present systematic review, all the relevant qualitative papers published from 2010 to October 2018, were examined. A  literature search was done in databases SID, Iran Medex, Iran doc, Magiran, Science Direct, Medline/PubMed, Web of Science, Scopus, ProQuest, Google Scholar, Cochran Library with keywords patient safety, surgical procedures, operative, checklist, World Health Organization, implementation science, qualitative research and their equivalent terms in Persian. Inclusion criteria were articles written in English or Persian, qualitative studies and relevant to the objectives of the study. Exclusion criteria were review articles, posters, presentations, letters to editor and quantitative studies. Results: The findings of the review of 14 qualitative studies showed that the most important challenges in effective implementation of the surgical safety checklist were unpredictable priorities, lack of collaboration and coordination of the surgical team members, mismatch between the checklist and hospital setting, lack of patient's cooperation and lack of a planned approach towards implementing the checklist. The strategies to improve the implementation of the surgical safety checklist included checklist localization, improving the collaboration and coordination of all the team members, training and practicing, patient participation, and active organizational leadership. Conclusion: The introduction of the surgical safety checklist to the health care setting is a permanent challenge and requires ongoing evaluations and its integration into the workflow in the hospital, active and effective leadership, explanation of why and how to use it by managers and receiving support from the organization. Continuous education, performance evaluation and the participation of all the surgical team members in the implementation of the checklist are key factors for effective implementation of the surgical safety checklist.